Investigating the Interplay Between Participation in a STEM-Focused Student Success Program and Workforce Participation on STEM Undergraduate Degree Completion - Ghazzawi, Dina; Pattison, Donna Lynn; Horn, Catherine Lynn (Frontiers in Sociology, 2022)
This study longitudinally tracks students participating in a STEM-focused intervention program to investigate workforce participation patterns and their association with degree completion in a STEM field. Using longitudinal data from the University of Houston's Education Research Center, this study examines the extent to which students participating in a STEM intervention program require additional work to fund tuition and other life expenses. Findings demonstrated a negative effect of workforce participation on college completion and showed that minority students were more likely to participate in the workforce while also receiving financial support from the STEM program compared to peers from other racial backgrounds. Results inform institutional and financial aid policies, as well as admission criteria as it relates to broadening access of under-represented students in STEM.